INOVASI MANAJEMEN KEGIATAN EKSTRAKURIKULER - Sri Nanti Sri Nanti (Manajer Pendididikan, 2017)
The general objective of this study was to describe the extracurricular activities ofmanagement innovationin Public Junior High School 02 Bingin Kuning Lebong Regency. Inparticular, this study aims to describe: innovation scouts extracurricular activities; innovationextracurricular arts activities; innovation of extracurricular activities sports; innovation religiousextracurricular activities. The research method used is descriptive qualitative. The result of thisresearch show that the management of innovation in extracurricular activities in school isnecessary in the implementation and development activities. Innovation committed inextracurricular activities can be done in terms of program activities, organizational structure,schedule of activities, administrative organization, facilities and infrastructure, and financingKeyword: extracurricular, innovation, management